solve by using splitting the middle term
Attachments:
![](https://hi-static.z-dn.net/files/d9c/5429516d8252ec1661de265810dc1eb3.jpg)
Answers
Answered by
1
Answer:
Step-by-step explanation:
= 6x^2+11x-35
= 6x^2-10x+21x-35
= 2x (3x-5)+7 (3x-5)
= (2x+7) (3x-5)
= 2x^2+13x+20
= 2x^2 8x+5x+20
= 2x (x+4)+5 (x+4)
= (2x+5) (x+4)
Answered by
1
Please mark me brainliest please buddy
Attachments:
![](https://hi-static.z-dn.net/files/d23/7b92924e7e43535fd687ff0441801dfc.png)
![](https://hi-static.z-dn.net/files/d26/bd922e82f512f65eeb00c513f02e4a00.jpg)
kmr99aashi:
Please mark me brainliest please buddy
Similar questions